MODELLING THE IMPACT OF URBANIZATION ON GROUNDWATER USING SYSTEM DYNAMIC TECHNIQUE. A CASE STUDY OF ARUSHA MUNICIPAL WELL FIELD IN NORTHEASTERN TANZANIA. - Kashimbiri, Nimzihirwa; Mtalo, Felix; Mwanuzi, Fredrick; Mandal, Nepal C; Singh, Vijay S (Tanzania Journal of Engineering and Technology, 2017)
This paper is concerned with the impact of urbanization in aquifer well-system located in the Municipal area of Arusha city, Tanzania. A system dynamic (SD) model was built under VENSIM PLE workbench from twenty-five years (1978-2003) physical and non-physical data to simulate their interactions and relations. This involved use of mathematics ideas and concepts in studying the physical and non €“ physical components separately, and finally putting them together in new form (model) and study their relations. After model was found to be structurally complete and simulate properly by using the model and unit check tool of VENSIMPLE, parametric calibration of the model follows. Model output results were then compared with existing field conditions and information ' s with the help of Excel spreadsheet. Historical data of population, rainfall, GDP, aquifer characteristics and land use was used as inputs. The model was trained for data series of 1978 to 1990 and examined for data series of 1990 to 2003. Model efficiency criteria R2, suggested by Nash and Sutcliffe (1970), produced good results ranging from 0.6333 to 0.9868 during calibration and 0.9833 to 0.9985 during verification. The model reveals that urbanization has enormous impact on population which was increasing at a rate of 4% from 1978 to 2003, which in turn caused increase in water demand for about 6% annually; as a result aquifer well-system was overstressed due to over-pumping. Lastly a prediction of the situation for 2025 was carried out in succession, and then interpretations and discussion concludes the paper.